Empowerment of Cadres and Health Workers in Foot Care (Foot Spa) in Diabetics - Ni Made Wedri; I Wayan Sukawana; I Made Sukarja (Universitas Muhammadiyah Palembang, 2023)
The number of DM sufferers continues to increase and is becoming a major health problem because of the economic burden, complications and difficulty in curating and the risk of amputation. The number of DM sufferers at the Abiansemal II Community Health Center was 167 people. Information was obtained from several sufferers saying their feet were tingling, dry and cracked heels, & they had never had foot care (foot spa), because they felt it was unnecessary. The service aims to increase understanding, awareness of cadres and people with diabetes about diabetic foot care to prevent foot ulcers. Service method with cadre assistance in empowering people with diabetes. Starting from giving a pre-test to cadres through a questionnaire, then providing counseling and training on diabetic foot care. Next, the cadres provide direct assistance to the diabetes in each Banjar, finally a post test is carried out on the cadres. The result was an increase in the knowledge and ability of cadres in diabetic foot care with a good category of 90% and a sufficient category of 10%. Independent foot spas should be continued by people with diabetes on an ongoing basis.